Identification of novel proteins associated with intelligence by integrating genome-wide association data and human brain proteomics - Zheng Zhang; Yousong Zhu; Junlong Zhang; Wenbin He; Cheng Han (PLoS ONE, 2025)
While genome-wide association studies (GWAS) have identified genetic variants associated with intelligence, their biological mechanisms remain largely unexplored. This study aimed to bridge this gap by integrating intelligence GWAS data with human brain proteomics and transcriptomics. We conducted proteome-wide (PWAS) and transcriptome-wide (TWAS) association studies, along with enrichment and protein-protein interaction (PPI) network analyses. PWAS identified 44 genes in the human brain proteome that influence intelligence through protein abundance regulation (FDR P <  0.05). Causal analysis revealed 36 genes, including GPX1, involved in the cis-regulation of protein abundance (P <  0.05). In independent PWAS analyses, 17 genes were validated, and 10 showed a positive correlation with intelligence (P <  0.05). TWAS revealed significant SNP-based heritability for mRNA in 28 proteins, and cis-regulation of mRNA levels for 20 genes was nominally associated with intelligence (FDR P <  0.05). This study identifies key genes that bridge genetic variants and protein-level mechanisms of intelligence, providing novel insights into its biological pathways and potential therapeutic targets.